2016
DOI: 10.1177/0266666915593620
|View full text |Cite
|
Sign up to set email alerts
|

Informationization of small-scale agribusinesses in rural areas of Korea

Abstract: Despite the significance of IT for small-scale agribusinesses (SSAs) in rural areas, little work has been done to identify the determinants of their informationization. Prior studies also overlook the social influences of informationization among SSAs in rural areas. Therefore, this study presents a model to explore and describe the roles played by institutional forces in the informationization of rural SSAs. To empirically test the presented model, partial least squares (PLS) analysis was conducted using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…According to Chin [41], the reliability of individual measures is ensured if the factor loading is higher than 0.7, and according to Fornell and Larker [42], if the average variance extracted (AVE) is greater than 0.5. If the square root of the AVE of each construct is greater than its correlation with the other constructs, the convergent validity is sufficient [42,43]. The results of convergent validities are seen in Table 1; the factor loadings of all measures are greater than 0.7 and the AVE scores for all variables are greater than 0.5.…”
Section: Methods and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Chin [41], the reliability of individual measures is ensured if the factor loading is higher than 0.7, and according to Fornell and Larker [42], if the average variance extracted (AVE) is greater than 0.5. If the square root of the AVE of each construct is greater than its correlation with the other constructs, the convergent validity is sufficient [42,43]. The results of convergent validities are seen in Table 1; the factor loadings of all measures are greater than 0.7 and the AVE scores for all variables are greater than 0.5.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Therefore, our measurement model demonstrates sufficient convergent validity and discriminant validity. According to a previous study [43], we also assessed whether education level varied by conducting ANOVA and found a significant difference among the four groups at the 0.1 level (F (1,292) = 3.383, p = 0.067). Therefore, we set education level as covariance and we conducted two-way analysis of covariance (ANCOVA) in Study 2.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Similarly, in this discussion on entrepreneurial capacities in the agricultural sector, the institutional context must guarantee various elements, such as an adequate legal framework to be able to collaborate with greater institutional certainty (Wincent et al, 2016), the rule of law (De Beer & Wunsch-Vincent, 2013), increased confidence in the figure of the farmer (Kang et al, 2016), as well as the relevant empowerment of their skills and knowledge (Camisón-Haba et al, 2019) in their training as an entrepreneur so that they take advantage of the business opportunities presented to them (Baur, 2020). As several authors have indicated (Sutter et al, 2019;Wang, 2020), for the undertaking capacity to be generated in the individuals engaged in agriculture, institutional arrangements must lead towards successful entrepreneurship decisions that guarantee cooperation, creating in an individual…”
Section: Introductionmentioning
confidence: 99%